Dampak Kemiskinan Terhadap Ketidaksetaraan Pelayanan Kesehatan di Indonesia - Maharani, Agisti; Astrid, Astrid; Arya, Arya; Deti, Deti; Yanti, Dewi; Sulla, Franklin Yohanes; Hafizi, M. Zainul (Yayasan Alpatih Harapan Semesta, 2023)
Poverty remains one of the significant issues affecting the quality of life in Indonesia, particularly in terms of access to healthcare services. Despite the government's various policies, such as the National Health Insurance (JKN), the poor still face serious barriers in terms of cost, distance, and infrastructure limitations. This inequality results in communities in rural or remote areas having greater difficulty accessing adequate healthcare compared to urban populations. This research employs a literature review method, analyzing various journal sources, reports, and publications over the past ten years. The findings indicate that poverty not only limits individuals' ability to meet basic needs but also exacerbates healthcare inequality, increasing vulnerability to chronic diseases due to delayed medical intervention. Therefore, policies focused on equitable distribution of medical personnel and healthcare facility development in underserved areas are essential.